PEMBERIAN MAKANAN PRALAKTASI DENGAN KELANGSUNGAN HIDUP BAYI DI INDONESIA (ANALISIS DATA SDKI 2007) - Utami Dewi (Jurnal Kesehatan, 2014)
Utami Dewi1)1)Jurusan Kebidanan Poltekkes Kemenkes TanjungpinangAbstract: Pre-Lacteal Feeds Toward Infant’s Survival In Indonesia (An Analysis On Idhs Data Year 2007).It is recommended for a mother to initiate to give early breastfeeding for a newborn as the first breast milk is known to be nutritious and contains antibody. The delay of breastfeeding shows that non breast milk-supplementary food is given. Based on BPS and Macro International data 65% of infants received pre-lacteal feeds besides breast milk in their three days of life.the known relationship between pre-lacteal feeds and infants’ survival in Indonesia.This was an observational study with a cohort retrospective study design by using IDHS data year 2007. Samples were all infants (<12 months, breastfed after birth) from mothers aged 15-49 years old as many as 15.679 mothers. The independent variable was pre-lacteal feeds after birth and the dependent variable was infants’ survival. The analyses used univariable, bivariable, and survival analysis with Kaplan-Meier and Log regression.Bivariable analysis using survival Kaplan-Meier showed that there was no significant relationship between pre-lacteal feeds after birth and infants’ survival. The survival of infants who received pre-lacteal feeds was greater than that of infants who did not receive pre-lacteal feeds (98.6%:99%).  Pre-lacteal feeds was not associated significant with an infant survival. Keyword: infant’s survival, pre-lacteal feeds, infant  Abstrak : Pemberian Makanan Pralaktasi dengan Kelangsungan Hidup Bayi di Indonesia (Analisis Data Sdki 2007).Disarankan bagi seorang ibu untuk memulai memberikan ASI dini untuk bayi yang baru lahir sebagai ASI pertama dikenal bergizi dan mengandung antibodi. Penundaan pemberian ASI menunjukkan bahwa non ASI-makanan tambahan yang diberikan Berdasarkan BPS dan data International Makro 65 % dari bayi menerima pre - lacteal feed selain ASI dalam tiga hari hidup mereka.Hubungan dikenal antara pra - lacteal feed dan kelangsungan hidup bayi di Indonesia.Ini merupakan penelitian observasional dengan desain penelitian retrospektif kohort dengan menggunakan SDKI tahun 2007. Data Sampel adalah semua bayi ( < 12 bulan , ASI setelah melahirkan ) dari ibu yang berusia 15 berusia -49 tahun sebanyak 15,679 ibu . Variabel bebas adalah pre - lacteal feed setelah lahir dan variabel terikat adalah kelangsungan hidup bayi. Analisis yang digunakan univariat, bivariat , dan analisis survival dengan Kaplan -Meier dan regresi Log.Analisis bivariabel menggunakan survival Kaplan - Meier menunjukkan bahwa tidak ada hubungan yang signifikan antara pre-lacteal feed setelah lahir dan kelangsungan hidup bayi. Kelangsungan hidup bayi yang menerima makanan pralaktasi lebih besar daripada bayi yang tidak menerima makanan pralaktasi ( 98,6 % : 99 % ). Makanan Pralaktasi tidak berhubungan signifikan dengan kelangsungan hidup bayi. Kata kunci : Kelangsungan hidup bayi , Makanan Pralaktasi, Bayi